2010
DOI: 10.1103/physreve.82.021508
|View full text |Cite
|
Sign up to set email alerts
|

Connection between slow and fast dynamics of molecular liquids around the glass transition

Abstract: The mean-square displacement (MSD) was measured by neutron scattering at various temperatures and pressures for a number of molecular glass-forming liquids. The MSD is invariant along the glass-transition line at the pressure studied, thus establishing an "intrinsic" Lindemann criterion for any given liquid. A one-to-one connection between the MSD's temperature dependence and the liquid's fragility is found when the MSD is evaluated on a time scale of ∼4 ns , but does not hold when the MSD is evaluated at shor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
33
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 77 publications
7
33
0
Order By: Relevance
“…In some liquids fast relaxation occurs at the nanosecond time scale [29], which will presumably contribute to the total entropy as well. This putative "fast relaxational" entropy term is not incorporated in this analysis.…”
mentioning
confidence: 99%
“…In some liquids fast relaxation occurs at the nanosecond time scale [29], which will presumably contribute to the total entropy as well. This putative "fast relaxational" entropy term is not incorporated in this analysis.…”
mentioning
confidence: 99%
“…The system size effects on these states will be discussed elsewhere. Experimental studies show a sudden change of slope in the temperature dependence of MSD at glass transition temperatures T g [7,8]. Extensive studies of non-diffusive states of systems of WCA spheres, revealed that temperature dependence of MSD shows a transition similar to those observed in experiments.…”
Section: Hopping Dynamics In Monodispersed Isotropic Spheresmentioning
confidence: 56%
“…Cumene has been studied for many years with other techniques, for example in Refs. 32,[43][44][45][46] . Cumene is a fragile liquid (m ≈ 70) with only a very small beta relaxation.…”
Section: The Experiments and Datamentioning
confidence: 99%
“…Since the thermal motion that gives rise to the transition is dominated by phonons, it is argued that the relevant time scale should be the picosecond time scale. However, for some liquids elastic models appear to work better when tested at longer time scales where the properties are more temperature dependent than at the phonon-times 32,33 . In other words, the temperature dependence of the vibration on the phonon time scale is not always large enough to account for the super-Arrhenius temperature dependence of the relaxation time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation